Бурозубка обыкновенная (Sorex araneus L.) Украинских Карпат - Сенык, А.Ф. (Вестник зоологии, 1972)
Morphological characters of Sorex araneus L. from the western regions of the Ukrainian SSR are very variable. In representatives of mountain populations of the given species some measurements of body and skull are greater and colour is much lighter. By mophological characters S. araneus L. of the Ukrainian Carpathians takes an intermediate place between two known subspecies - Sorex araneus araneus L. and S. araneus tetragonu- rus Herm.